Healing smiles: Enhancing pediatric dental care through animal-assisted therapy – A narrative review - Aishwarya Vineshkumar Antala; Pratik B Kariya (Archives of Medicine and Health Sciences, 2023)
Dental anxiety refers to the negative emotional response of fear or avoiding dental care, which is exhibited by cognitive, physiological, and motor reactions when related to dental visits or dental treatment. Diverse approaches have been put forth to manage these adverse reactions during dental treatment, with the main emphasis on nonpharmacological and pharmacological management or altering the environment. Animal-assisted therapy (AAT) has been suggested as an alternative to conventional methods that, according to prior research on human-animal interactions, has soothing benefits for individuals. Numerous articles have shown that activities involving pets help to lessen tension in dental practice. A trained animal is used in health care as a goal-oriented intervention to enhance interactions or lessen a patient's fear and discomfort. AAT appointments are arranged for a set time and duration to include an animal that has completed temperament testing, intensive training, and certification, in contrast to animal-assisted activities. The companion animal, which is available for the company throughout the dentist appointment, can assist in removing barriers to communication and enabling the patient to build a secure and soothing bond, minimizing treatment-related stress. By conducting this review, we would like to emphasize on benefits and obstacles of AAT for behavior management in pediatric dental procedures.